1994
DOI: 10.1136/jnnp.57.11.1334
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex encephalitis: long term magnetic resonance imaging and neuropsychological profile.

Abstract: The first comprehensive in vivo documentation of the long term profile of pathological and spared tissue is described in a group of 10 patients with a diagnosis of herpes simplex encephalitis, who were left with memory difficulties as a major residual sequel of their condition. With a dedicated MRI protocol, which included high resolution images of temporal lobe and limbic system areas, data are provided on structures that have recently gained importance as anatomical substrates for amnesia. The major features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(111 citation statements)
references
References 27 publications
2
108
0
1
Order By: Relevance
“…The proclivity of viral infection sequelae for the temporal lobes may explain the robust memory deficits found in some patients with HSV encephalitis during neuropsychological testing (Gordon et al, 1990;Kapur et al, 1994). However, when we tested adult rats with a history of brain inflammation, they showed only mild deficits in behaviours mediated by mesial temporal lobe structures.…”
Section: Discussionmentioning
confidence: 91%
“…The proclivity of viral infection sequelae for the temporal lobes may explain the robust memory deficits found in some patients with HSV encephalitis during neuropsychological testing (Gordon et al, 1990;Kapur et al, 1994). However, when we tested adult rats with a history of brain inflammation, they showed only mild deficits in behaviours mediated by mesial temporal lobe structures.…”
Section: Discussionmentioning
confidence: 91%
“…Diffusion-weighted abnormalities in herpes encephalitis include bilateral, asymmetrical regions of diffusion-weighted hyperintensity involving the medial temporal lobes and inferior frontal lobes, with relative sparing of the basal ganglia and white matter [18] (Figure 4). Although, typically, there is corresponding T 2 hyperintensity, several studies have suggested that the diffusionweighted signal changes are more sensitive than those on conventional MR sequences [19,20].…”
Section: Infectious Viral Herpes Encephalitismentioning
confidence: 99%
“…El daño infl amatorio y el edema que se produce durante HSE ocurre en el lóbulo frontal y el lóbulo temporal incluyendo el sistema límbico 10,13 . Al respecto, se ha encontrado la presencia de antígenos virales de HSV en cerebros de pacientes fallecidos por HSE concentrados principalmente en los lóbulos temporal inferior y medio, hipocampo, amígdala, corteza olfatoria, ínsula y giro cingulado 14,15 .…”
Section: Infección Del Sistema Nervioso Central Por Hsv-1unclassified